Pengaruh makro ekonomi dan fundamental perusahaan terhadap kinerja perbankan syariah di Indonesia - Soeharjoto Soeharjoto; Dini Hariyanti (Penerbit Goodwood, 2019)
Purpose: To find out the influence of macroeconomic and company fundamentals on sharia banking performance in Indonesia. Research Methodology: The regression test was used to analyze the monthly data of BI, BPS, and OJK in 2014-2018. Independent variable of macroeconomic was proxied by inflation, exchange rate, GDP; corporate fundamentals by CAR, FDR, BOPO, NPF, DPK; while performance as dependent variable by ROA. Results: Inflation and BOPO negatively and significantly influence ROA; while the exchange rate, GDP, CAR, NPF, DPK, FDR are not significant. Limitations: This research was conducted in the Islamic banking industry in Indonesia by using the variables of the company fundamentals and macroeconomics. Contribution: This research is useful for policy-making and research of sharia banking in Indonesia. Keywords: Performance, Macroeconomics, Corporate fundamentals